Throw out the Map: Neuropathogenesis of the Globally Expanding California Serogroup of Orthobunyaviruses - Alyssa B. Evans; Karin E. Peterson (Viruses, 2019)
The California serogroup (CSG) comprises 18 serologically and genetically related mosquito-borne orthobunyaviruses. Of these viruses, at least seven have been shown to cause neurological disease in humans, including the leading cause of pediatric arboviral encephalitis in the USA, La Crosse virus. Despite the disease burden from these viruses, much is still unknown about the CSG viruses. This review summarizes our current knowledge of the CSG viruses, including human disease and the mechanisms of neuropathogenesis.